De novo variants in CELF2 that disrupt the nuclear localization signal cause developmental and epileptic encephalopathy - Itai, Toshiyuki; Hamanaka, Kohei; Sasaki, Kazunori; Wagner, Matias; Kotzaeridou, Urania; Brösse, Ines; Ries, Markus; Kobayashi, Yu; Tohyama, Jun; Kato, Mitsuhiro; Ong, Winnie P.; Chew, Hui B.; et al. (Human mutation, 2021)
We report heterozygous CELF2 (NM_006561.3) variants in five unrelated individuals: Individuals 1-4 exhibited developmental and epileptic encephalopathy (DEE) and Individual 5 had intellectual disability and autistic features. CELF2 encodes a nucleocytoplasmic shuttling RNA-binding protein that has multiple roles in RNA processing and is involved in the embryonic development of the central nervous system and heart. Whole-exome sequencing identified the following CELF2 variants: two missense variants [c.1558C>T:p.(Pro520Ser) in unrelated Individuals 1 and 2, and c.1516C>G:p.(Arg506Gly) in Individual 3], one frameshift variant in Individual 4 that removed the last amino acid of CELF2 c.1562dup:p.(Tyr521Ter), possibly resulting in escape from nonsense-mediated mRNA decay (NMD), and one canonical splice site variant, c.272-1G>C in Individual 5, also probably leading to NMD. The identified variants in Individuals 1, 2, 4, and 5 were de novo, while the variant in Individual 3 was inherited from her mosaic mother. Notably, all identified variants, except for c.272-1G>C, were clustered within 20 amino acid residues of the C-terminus, which might be a nuclear localization signal. We demonstrated the extranuclear mislocalization of mutant CELF2 protein in cells transfected with mutant CELF2 complementary DNA plasmids. Our findings indicate that CELF2 variants that disrupt its nuclear localization are associated with DEE.
First published: 01 November 2020
Gesehen am 25.05.2021